2007
DOI: 10.1177/021849230701500404
|View full text |Cite
|
Sign up to set email alerts
|

Does Tranexamic Acid Reduce Blood Loss in Off-Pump Coronary Artery Bypass?

Abstract: The hemostatic effect of tranexamic acid on the bleeding tendency and transfusion requirements in patients undergoing off-pump coronary artery bypass surgery was assessed in a prospective randomized double-blind study. Of 66 patients undergoing elective operations, 33 were given tranexamic acid (15 mg x kg(-1) before infusion of heparin and 15 mg x kg(-1) after protamine infusion), and the other 33 received only saline. Postoperative bleeding, transfusions, complications, hematological variables, and plasma D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…[1] Though OPCAB surgeries are associated with fewer complications, bleeding continues to be an issue that requires to be addressed. [2,3] Hemodynamic management during OPCAB by the administration of boluses of intravenous fluids and the properties of these fluids contributing to hemorheological stability remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Though OPCAB surgeries are associated with fewer complications, bleeding continues to be an issue that requires to be addressed. [2,3] Hemodynamic management during OPCAB by the administration of boluses of intravenous fluids and the properties of these fluids contributing to hemorheological stability remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] The search for the newer modes to facilitate reduction in perioperative blood loss continues, the use of fibrinolytic inhibitors such as TA may be an effective method to promote blood conservation; but, the possible complications of thrombosis of coronary artery graft, precludes their regular use in coronary artery bypass graft surgeries. [1,6,7] In this study we assessed the hemostatic effects of concomitant use of HES and TA. Thromboelastogram (TEG) was used to assess the hemostatic effect of the combination of HES and TA.…”
Section: Introductionmentioning
confidence: 99%
“…Tranexamic acid has been widely and successfully used to reduce bleeding in cardiac [4][5][6], orthopaedic [7,8], prostate [9] and caesarean sections surgeries [10,11]. In this study we plan to verify the efficacy of tranexamic acid in reducing tonsillectomy bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Each of these randomized trials compared tranexamic acid with placebo or inactive control, and each measured blood loss or transfusions as a primary endpoint. Only 1 of the 8 trials of tranexamic in OPCAB found a significant reduction in the risk of allogeneic blood product exposure.…”
mentioning
confidence: 99%